PRAME Staining of Adnexal Lesions and Common Skin Cancer Types: Biomarker with Potential Diagnostic Utility - Hisham F. Bahmad; John Alexis (Dermatopathology)
PRAME (PReferentially expressed Antigen in MElanoma) is a tumor-associated antigen first identified in tumor-reactive T-cell clones derived from a patient with metastatic melanoma. Immunohistochemistry (IHC) for PRAME is useful for diagnostic purposes to support a suspected diagnosis of melanoma. Anecdotally, PRAME has been observed to stain sebaceous units in glands in background skin. We examined the expression of PRAME in adnexal lesions and common skin cancers to determine whether it is of potential diagnostic utility in supporting the differentiation between sebaceous and non-sebaceous lesions. IRB approval from Mount Sinai Medical Center (MSMC) was obtained. This is a single-center retrospective cohort analysis over a ten-year period (1 January 2012, and 31 December 2023). We used the pathological database of skin lesions, including sebaceous, sweat gland, and follicular lesions, in addition to basal cell carcinomas (BCCs) and squamous cell carcinomas (SCCs), from 81 patients who underwent shave/punch biopsies or surgical excisions. We evaluated the IHC staining percentage positivity and intensity for PRAME. Staining intensity was subcategorized into negative, weak, moderate, and strong, whereas expression percentage positivity was subcategorized into 0%, 1–25%, 26–50%, 51–75%, and 76–100%. Most sebaceous versus non-sebaceous lesions exhibited cytoplasmic staining of moderate to strong intensity in >75% of cells. PRAME has a sensitivity and specificity of 100.0% and 86.7%, respectively, to support distinguishing between sebaceous and non-sebaceous adnexal lesions (regardless of whether they are benign or malignant). BCCs and SCCs showed weak to moderate nuclear staining for PRAME in >75% of cells. None of the 13 lesions of hair follicle origin showed any staining. A total of 26 of the 32 lesions of sweat gland origin were negative while 6 (18.75%) showed positive staining. In conclusion, we confirm the potential utility of PRAME for supporting the distinction between sebaceous and non-sebaceous adnexal lesions on one hand, and on the other, distinguishing BCC and SCC that may show nuclear staining from sebaceous carcinoma that shows cytoplasmic staining.